NAD+ and NADH regulate an ATP-dependent kinase that phosphorylates enzyme I of the Escherichia coli phosphotransferase system. - Dannelly, H K (1992)
Crude extracts of Escherichia coli contain a protein kinase, EI-K, that phosphorylates enzyme I (EI) of the phosphoenolpyruvate:glycose phosphotransferase system (PTS). Phosphorylation occurs at the active site histidine residue. The activity of EI-K was lost during purification. However, kinase activity was restored by adding NAD+ or NADP+.NADH reversed NAD+ activation of the kinase, and the level of EI-K activity was dependent on the NAD+/NADH ratio. Although crude preparations of EI-K showed no NAD+ requirement, they were completely inhibited by NADH, either in the assay mixture or when the enzyme was pretreated and the NADH was removed prior to the assay. NAD+ restored full activity to the NADH-pretreated inactive fractions. The results suggest that EI-K contains a bound cofactor that is lost during purification and that may be analogous to NAD+. EI-K activity may serve to link some of the diverse functions of the PTS, such as sugar transport, to the metabolic state of the cell.